Transmission of SARS-CoV-2 in the workplace: Key findings from a rapid review of the literature. Issue 3 (4th March 2023) - Cox, Jennie; Christensen, Brian; Burton, Nancy; Dunn, Kevin H.; Finnegan, Mikaela; Ruess, Ana; Estill, Cherie
Abstract: At the beginning of the COVID-19 pandemic, the primary route of transmission of the SARS-CoV-2 virus was not well understood. Research gathered from other respiratory infectious diseases, including other coronaviruses, was the basis for the initial perceptions for transmission of SARS-CoV-2. To better understand transmission of SARS-CoV-2, a rapid literature review was conducted from literature generated 19 March 2020, through 23 September 2021. 18, 616 unique results were identified from literature databases and screened. Of these, 279 key articles were reviewed and abstracted covering critical topics such as environmental/workplace monitoring, sampling and analytical method evaluation, and the ability of the virus to remain intact and infectious during sampling. This paper describes the results of the rapid literature review, which evaluated pathways that contribute to transmission as well as the strengths and limitations of current sampling approaches. This review also evaluates how different factors, including environmental conditions and surface characteristics, could impact the transmission potential of SARS-CoV-2. A continual rapid review in the midst of a pandemic proved particularly useful for quickly understanding the transmission parameters of the virus and enabled us to comprehensively assess literature, respond to workplace questions, and evaluate our understanding as the science evolved. Air and surface sampling with the accompanying analytical methods were not generally effective in recovering SARS-CoV-2 viable virus or RNA in many likely contaminated environments. In light of these findings, the development of validated sampling and analysis methods is critical for determining worker exposure to SARS-CoV-2 and to assess the impact of mitigation efforts. Copyright © 2023 American Association for Aerosol Research